Les mosquées ibadites du Maghreb - Virginie Prevost (Revue des Mondes Musulmans et de la Méditerranée)
The Ibadite mosques of Mzab, Jebel Nafûsa and Djerba share a number of characteristics, the most important being the multiplicity of mihrabs and prayer niches outside of the sanctuary. In Mzab, the mosques are especially recognizable for their high, Saharan style minarets and absolute respect for two Ibadite peculiarities: the absence of minbar and the rejection of decorative finishes. In Jebel Nafûsa and Djerba, the mosques, which are sometimes underground, look alike and are very modest. Minarets, if they exist at all, present a diversity of styles. Quite a few sanctuaries display traditional Berber geometrical motifs. Djerban mosques, the architecture of which is closely related to the community’s insularity, are especially interesting for having been incorporated into the island’s defensive works, as well as for the variety of late decorative elements and the frequent staircase minaret which has been preserved through the ages.